PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Survey Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015 – 2019 ) - Evilia Sri Yuniar; Irly Artiara Irawan (LP2M Universitas Perjuangan Tasikmalaya, 2022)
This study aims to analyze how profitability, debt policy, dividend policy firm value and to analyze the effect of profitability, debt policy and dividend policy on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2019 either partially or simultaneously. The research method used is a quantitative method. The research sample is 26 manufacturing companies listed on the Indonesia Stock Exchange for the period 2015 – 2019. The research data used is secondary data, namely the company's annual financial report data which is analyzed by panel data regression. The results show that partially profitability, debt policy and dividend policy have a positive effect on the value of manufacturing companies listed on the Indonesia Stock Exchange for the 2015 - 2019 period. Meanwhile, simultaneously profitability, debt policy and dividend policy affect the value of manufacturing companies listed on the Stock Exchange. Indonesia Securities Period 2015 – 2019.